2021
DOI: 10.4103/jfmpc.jfmpc_2481_20
|View full text |Cite
|
Sign up to set email alerts
|

Oral Health Status and Treatment Need in Geriatric Patients with Different Degrees of Cognitive Impairment and Dementia

Abstract: Background: Health can be defined as more than an absence or lack of disease. It is generally related to personal, physical, social, along with spiritual wellness. However, the importance of good health is comparable with a progressive physical and cognitive limitations due to aging and hence, its clear definition is not possible. Hence, most of the important aims or goals in aging are unrelated to finding a cure but rather toward achieving an optimal function. Thus, a healthy aging process that e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…Good oral health is a critical factor in healthy ageing, associated with general health, morbidity and mortality in older people (Lauritano et al, 2019). Many studies have reported that oral disease is a risk factor for cardiovascular disease, cancer, chronic respiratory disease and cognitive impairment, affecting overall health (Kang et al, 2020; Kumar et al, 2021; Zhang et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Good oral health is a critical factor in healthy ageing, associated with general health, morbidity and mortality in older people (Lauritano et al, 2019). Many studies have reported that oral disease is a risk factor for cardiovascular disease, cancer, chronic respiratory disease and cognitive impairment, affecting overall health (Kang et al, 2020; Kumar et al, 2021; Zhang et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…is a risk factor for cardiovascular disease, cancer, chronic respiratory disease and cognitive impairment, affecting overall health (Kang et al, 2020;Kumar et al, 2021;Zhang et al, 2021).…”
mentioning
confidence: 99%
“…Mental health can be defined as more than an absence or lack of mental disorders (Kumar et al, 2021). It is generally related to physical, social, and spiritual wellness, including positive moods, such as happiness.…”
Section: Introductionmentioning
confidence: 99%